دور الزكاة المنتجة في خدمة المجتمع و نقصان الفقراء وتحسين الاقتصاد الاندونيسي (ZISWAF: Jurnal Zakat dan Wakaf, 2018)
This article aims at showing the role of productive zakat in reduce poverty and improving the economy of Indonesian society. This study is based on field research using the phenomenological approach. The method of data analysis used the analysis of the content on the messages received from the productive zakat. Zakat as a religious law, and a unique unity that combines educational functions with social purposes and economic realities require further study to discover more of its legislative secrets and to find out about its various miraculous aspects. One of the purposes of zakat legislation is to provide the necessary sufficiency to dispense with it, the person who is poor and in need, and for the Muzakki, he treats himself in a small way and distorts the instinct of ownership, so that he becomes accustomed in giving and spending for zakat. The attempt to remove usury without activating the zakat foundation leads to a fundamental flaw in the Islamic finance process, To regulate or at the level of practice making usury tricks it appears as a necessity that can not escape them, though, in fact, the problem does not only make matters worse.